All Days 2013
DOI: 10.2118/167053-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hydraulic Fracture Geometry by Directional Drilling in a Coal Seam Gas Formation

Abstract: Hydraulic fracturing has been widely used to develop coal seam gas (CSG) resources worldwide and improve gas production from CSG wells. An optimal stimulation in CSG, in particular with lower permeability coals lacking a well-developed cleat system, creates a fracture with sufficient length and orientation along the maximum horizontal stress (σHmax) direction such that the fracture intersects the existing hydraulically-conductive natural fracture network in an a way that maximizes the stimulation effect. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The report of this experiment was documented in three papers and included: (i) results of DFITs for stress and permeability (see Figure 9); (ii) geomechanical studies; (ii) use of advanced pre-and post-frac sonic anisotropy logs and radioactive tracers for frac height determination; and (iii) hydraulic fracture history-matching of bottomhole treating pressure, surface deformation tiltmeter, and downhole microseismic monitoring data (see Figure 10) (Johnson et al 2010a, Johnson et al 2010b, Scott et al 2010)(see Figure 10). The end determination of this and subsequent studies by QGC (Megorden, Jiang and Bentley 2013) was that sub-economic productivity largely resulted from the formation of a complex fracture, which poorly interconnected and instead directly stimulated a sparse and predominantly unidirectional natural fracture system in the WCM in this area of the Surat Basin. Similar results as well as overall poor responses due to low permeability Recently, a positive experience was reported by QGC using a different strategy when revisiting a problematic area, which had similar fracturing behavior to the Ridgewood site (e.g., microseismic, tiltmeter, sonic anisotropy, and radioactive tracer data) but overall high productivity.…”
Section: Chinchilla/goondiwindi Slope Project Areasmentioning
confidence: 91%
See 1 more Smart Citation
“…The report of this experiment was documented in three papers and included: (i) results of DFITs for stress and permeability (see Figure 9); (ii) geomechanical studies; (ii) use of advanced pre-and post-frac sonic anisotropy logs and radioactive tracers for frac height determination; and (iii) hydraulic fracture history-matching of bottomhole treating pressure, surface deformation tiltmeter, and downhole microseismic monitoring data (see Figure 10) (Johnson et al 2010a, Johnson et al 2010b, Scott et al 2010)(see Figure 10). The end determination of this and subsequent studies by QGC (Megorden, Jiang and Bentley 2013) was that sub-economic productivity largely resulted from the formation of a complex fracture, which poorly interconnected and instead directly stimulated a sparse and predominantly unidirectional natural fracture system in the WCM in this area of the Surat Basin. Similar results as well as overall poor responses due to low permeability Recently, a positive experience was reported by QGC using a different strategy when revisiting a problematic area, which had similar fracturing behavior to the Ridgewood site (e.g., microseismic, tiltmeter, sonic anisotropy, and radioactive tracer data) but overall high productivity.…”
Section: Chinchilla/goondiwindi Slope Project Areasmentioning
confidence: 91%
“…Similar results as well as overall poor responses due to low permeability Recently, a positive experience was reported by QGC using a different strategy when revisiting a problematic area, which had similar fracturing behavior to the Ridgewood site (e.g., microseismic, tiltmeter, sonic anisotropy, and radioactive tracer data) but overall high productivity. In this case, QGC drilled two wells at 27.5 and 6 deg deviation in the H-Max direction and saw improved containment in the targeted intervals as well as improved fracture length in the H-Max direction resulting in noticeable but still uneconomic improvements in production relative to offset vertical, hydraulically fractured, producers (Megorden et al 2013) (See Figure 11). This study documents the use of microseismic, tiltmeter, and pressure transient data that confirmed this effect within close proximity to the prior campaigns failed multi-stage treatment using a similar pumping schedule in a vertical wellbore.…”
Section: Chinchilla/goondiwindi Slope Project Areasmentioning
confidence: 99%
“…Then the Galerkin method is used to make the left polynomials of the Formulas (2) and (3) respectively to substitute A and B of Equation (5), and substitute the shape function constructed by ε and p o in Equation (4) into Equation (5). Making a = −b, the deformation formula is simplified as follows:…”
Section: Finite Element Discretization Methods and Stress-seepage Coupmentioning
confidence: 99%
“…The reservoir simulation technology of radial boreholes combined with hydraulic fracturing is an innovative technology to effectively develop low-permeability, thin-layer, fractured reservoirs, water-flooded 'dead oil areas' and lithologic trap reservoirs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, radial drilling-fracturing, the combination of the hydraulic fracturing and radial borehole, is proposed [6]. This technology integrates the merits both of hydraulic fracturing and radial drilling, guiding the hydraulic fracture toward the target area with radial borehole and, meanwhile, enhancing the wellbore-reservoir contact area significantly [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%